Design of a Performance-Based Progressive Sanction System to Prevent State Losses in Non-Compliance of Local Government Financial Reports (LKPD) - Dwi Novemyanto, Alfin; Riawan Tjandra, W. (Policy, Law and Political Research Center, 2025)
Non-compliance with the provisions of laws and regulations in the 2023 Local Government Financial Statements (LKPD) caused potential state losses of IDR 2.45 trillion with 4,147 findings spread across 543 entities. The existing administrative sanction system has proven ineffective because it is normative, not tiered, and has no real fiscal consequences. This research aims to formulate a performance-based progressive sanction system design that is able to improve compliance and prevent systemic state losses. The method used is normative legal research with a statutory and conceptual approach, and uses the Responsive Regulation theory from Ayres and Braithwaite as a foundation in developing a sanction escalation model based on the behavior of the supervised entity. The results show the need for regulations that contain performance indicators, classification of violations, fiscal incentives or disincentives, and an integrated data-based supervision system. The novelty of this research lies in the formulation of a sanction system that combines corrective and educative functions, different from previous research that only focuses on quantitative or managerial aspects. The scientific contribution of this article lies in strengthening administrative law as a means of enforcing fiscal compliance and as a regulative solution to regional financial leakage. As such, this research provides a normative foundation for a more equitable, proportional, and results-based reform of the regional financial oversight system.